THE RELATION BETWEEN MOTHER’S BEHAVIOR REGARDING FORMULA FEEDING AND DENTAL CARIES IN PRESCHOOL CHILDREN - Anisa Rahmawati; Hadiyat Miko; Eliati Sri Suharja (Jurusan Keperawatan Gigi Poltekkes Kemenkes Tasikmalaya, 2023)
Background: The national prevalence of dental and oral health problems is 57.6%. In the age group 3-4 years the percentage of those who experienced dental caries was 81.5%. Whereas in the age group 5-9 years it was 92.6%. There are many causes of caries in milk teeth, one of which is formula milk. Parents especially mothers play a very important role in giving formula milk to children. Purpose: this study aims to analyze the relationship between mother’s behavior regarding formula feeding and dental caries in preschool-aged children at TK Tunas Ciremai Giri, Cirebon City. Methods: this study used a cross-sectional study design. The population in this study were children from Kindergarten Tunas Ciremai Giri Cirebon City and their mothers totaling 130 people with a total sample of 38 people each and using a purposive sampling technique. The measuring tool for this study was a questionnaire to determine the behavior of mothers regarding formula feeding and caries examination using the def-t index. Data analysis used the Spearman Rank test. Results: mother's behavior regarding giving formula milk was included in the sufficient and good category for the same number of 19 respondents (50%) in each category and the majority of children who experienced caries were in the low category of 15 children (39.5%). Spearman's Rank test results obtained a significance value of 0.001 where sig 0.05. Conclusion: there is a relationship between mother's behavior regarding formula feeding and dental caries in preschool children at Tunas Ciremai Giri Kindergarten, Cirebon City.